Estimation of prevalence of gingival enlargement - a population- based study - KALAIVANI N.,; DR. N.D. JAYAKUMAR,; MAHESH RAMAKRISHNAN., (The journal of contemporary issues in business and government, 2020)
Gingival enlargement is an increase in the size of the gingiva. It is also known as the gingival hyperplasia or hypertrophy. They can be categorised based on their etiology, pathogenesis, location, size and extent. Inflammatory gingival enlargement is a most common form and clinically present as soft and discolored gingiva. Drug induced gingival enlargement is a well recognised adverse effect of certain systemic medications. Calcium channel blockers, Anticonvulsants and Immunosuppressants are frequently implicated drugs in the etiology of drug induced enlargement. The aim of the study is to assess the prevalence of gingival enlargement and its distribution. Objective: To assess the prevalence of inflammatory and drug induced To compare the prevalence of gingival enlargement in different age To compare the prevalence of gingival enlargement in male and female. To compare the prevalence of gingival enlargement in response to different types of The study was a retrospective, University based study. Case sheets of patients visiting the dental outpatient ward June 2019 to March 2020 were collected. Patients diagnosed with gingival enlargement were sorted and tabulated in Microsoft excel sheet and analysed using SPSS software. In the present study, out of 40,000 patients, the prevalence of inflammatory enlargement was found to be 0.1% and the drug induced enlargement was 0.03%. Drug induced enlargement was more prevalent in males than in females, whereas inflammatory enlargement was more prevalent in females than males, there was no statistically significant difference in the prevalence rate between age groups (p= 0.362) and gender (p= 0.210). On comparing the drugs, phenytoin was consumed by one third of the population (43%) but had a higher prevalence rate of 65% than antihypertensive drugs (28% )and immunosuppressants (7% ).